The Origin of Felsic Intrusions Within the Mantle Section of the Samail Ophiolite: Geochemical Evidence for Three Distinct Mixing and Fractionation Trends. Issue 5 (24th May 2021) - Rioux, Matthew; Benoit, Mathieu; Amri, Isma; Ceuleneer, Georges; Garber, Joshua M.; Searle, Michael; Leal, Kayla
Abstract: An isotopically diverse suite of felsic dikes, sills, and plugs (εNd (t) = −7.8 to +7.8) intrude the uppermost mantle and lower crust in the Samail ophiolite in Oman and the United Arab Emirates (UAE). These features have been interpreted to represent amphibolite and metasediment melts from an underthrust sheet of oceanic lithosphere. As such, the intrusions provide a record of melting of oceanic crust and sediment at depth, with implications for mass transfer from the down‐going plate in young, hot subduction settings. Several studies have used geochemical data to constrain the magmatic sources of the dikes; here we build on this previous work using integrated whole rock major element, trace element and Nd isotopic data from a more geographically extensive suite of dikes. New and existing data suggest the felsic intrusions preserved within mantle peridotites in the Oman portion of the ophiolite were generated by three distinct mixing and fractionation trends: (1) three‐component mixing between sediment melt, amphibolite melt and a mantle component; (2) two component mixing between amphibolite and sediment melts, with little mantle contribution; and (3) fractional crystallization of depleted, mantle derived magmas, likely related to the ophiolite V2 volcanic series. Combined geochemical and pseudosection modeling suggest that amphibolite melting occurred at P ≤ 1.4 GPa (∼40–45 km) and T ≥ 700–750°C. Felsic intrusions in the mantle section in the UAE, including garnet‐andalusite‐cordierite leucogranites, follow similar mixing trends, but crystallized ∼0.9–4.0 Ma after the Oman intrusions. Key Points: Felsic dikes and sills with epsilon Nd of −7.8 to +7.8 intruded the shallow mantle in the Samail ophiolite Combined whole rock major element, trace element, and isotopic data define three distinct mixing and fractionation trends Most dikes formed by sediment and amphibolite melting on underthrust oceanic lithosphere at P ≤ 1.4 GPa and T ≥ 700–750°C